Optimization of hydrogen production process by response surface methodology - Saifuddin N.; Priatharsini P.; Ong M.Y. (Medwell Journals, 2023)
Enhancement of bio-hydrogen production by green microalgae Chlamydomonas reinhardtii has captivated tremendous interest. The yield of bio-hydrogen production by C. reinhardtii was enhanced by co-culturing with ragi tapai followed by immobilization and culturing in the right TAP-S medium. In this study, the three factors that affects the bio-hydrogen production by C. reinhardtii were evaluated with Response Surface Methodology (RSM). The amount of microalgae and ragi tapai as well the pH of the culture medium were simultaneously altered to determine the maximum bio-hydrogen yield. The maximum bio-hydrogen production yield obtained was 702317 ppm under conditions of 2.46 g of microalgae, 0.45 g of ragi tapai and pH medium of 7.23. Medwell Journals, 2017.